Educating queer sexual citizens? A feminist exploration of bisexual and queer young women's sex education in Tasmania, Australia. Issue 3 (4th May 2019) - Grant, Ruby; Nash, Meredith
ABSTRACT: There is a well-documented absence of inclusive school-based sex and relationships education (SRE) for Australian lesbian, gay, bisexual, transgender, and queer (LGBTQ) youth. Moreover, relatively few studies specifically examine how bisexual and queer-identifying young Australian women experience SRE. This qualitative study addresses the gap and contributes new perspectives by examining bisexual and queer young women's experiences of school-based SRE in the state of Tasmania through the lens of sexual citizenship. Drawing on qualitative interviews with 15 Tasmanian bisexual and queer young women, we argue that biomedical, risk-based and heteronormative approaches to SRE reduce young women's sexual health literacy. By framing SRE around the concept of 'sexual citizenship', this article provides important guidance on how SRE can more effectively provide bisexual and queer young women with the skills they need to be effective, engaged sexual citizens.